The Effect of “Carvacrol” on Ischemia-Reperfusion Injury in the Skeletal Muscles of Rats - Barış Mardin; Abdullah Özer; Başak Koçak; Ayşegül Küçük; Mustafa Hakan Zor; Şaban Cem Sezen; Mustafa Kavutçu; Mustafa Arslan; Gürsel Levent Oktar (Gazi Medical Journal)
Objective: Ischemia is characterized by an inadequate supply of nutrients and oxygen due to reduced blood circulation to specific tissues or organs. Reperfusion injury refers to the detrimental effects of abrupt exposure of the ischemic tissue to elevated oxygen levels and subsequent generation of reactive oxygen derivatives inside the tissue. In surgical procedures characterized by frequent occurrences of ischemia-reperfusion (I/R), such as transplant and cardiovascular surgery, it is crucial to prioritize the preservation of tissue integrity and mitigation of associated damage. In this study, we formulated a hypothesis suggesting that carvacrol (Car), an aromatic hydrocarbon present in some plant species, might decrease I/R injury by implication of its antioxidant, anti-apoptotic, and anti-inflammatory functions. Methods: We planned our study with 18 rats, randomly divided into three groups: control group, I/R group, and I/R + Car group. In the control group, laparotomy was performed only, and blood and lower limb muscle tissue samples were taken. In the I/R group, after laparotomy, lower extremity ischemia is achieved for 60 min, and reperfusion is achieved for another 60 min. In I/R + Car, rats were administered 100 mg/kg Car via intraperitoneal injection 30 min after ischemia. Then, 60 min of ischemia and 60 min of reperfusion were achieved. Lower limb muscle samples were examined both histologically and biochemically. We evaluated the levels of malondialdehyde (MDA), glutathione-S transferase (GST), and catalase (CAT). In addition, serum ischemia-modified albumin (IMA) levels were measured. Results: Our study showed that the findings of I/R injury decreased prominently in the I/R + Car group’s samples. GST, MDA, CAT, and IMA levels were significantly higher in the I/R group than in the control and I/R + Car groups. (p=0.024, p=0.010, p=0.030 and p<0.0001; respectively). Histopathological examination revealed no degeneration in the control group. Conversely, contraction, hypertrophy, nucleus degeneration, necrotic fibers, and hyalinization were observed in the I/R group. In the I/R + Car group, inflamed areas were less frequent than in the I/R group, and vascular dilatation of myofibre was noted. Conclusion: This study demonstrates that the Car molecule protects against I/R injury. Therefore, we contend that more experimental cohort investigations are needed to examine the impact of the Car molecule on preventing I/R injury.